United Republic of Tanzania : Poverty Reduction Strategy Paper; Annual Implementation Report 2006/07. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The MKUKUTA Annual Implementation Report (MAIR) is one of the outputs of the Tanzanian government's monitoring system. The objective of this report is to contribute to all government reporting systems, which include output reporting by Ministries, Departments and Agencies, Local Government Authority, and non-state actors implementing MKUKUTA activities. It is based on analysis of progress at the goal level, and provides an overview of performance, challenges, lessons learned, and next steps within each MKUKUTA cluster. It also includes progress on other processes and reforms and how these have contributed to achievements of MKUKUTA outcomes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet